2015
DOI: 10.1051/0004-6361/201526111
|View full text |Cite
|
Sign up to set email alerts
|

New atmospheric parameters and spectral interpolator for the MILES cool stars

Abstract: Context. The full spectrum fitting of stellar spectra against a library of empirical spectra is a well-established approach to measure the atmospheric parameters of FGK stars with a high internal consistency. Extending it towards cooler stars still remains a challenge. Aims. We address this question by improving the interpolator of the Medium-resolution INT Library of Empirical Spectra (MILES) library in the low effective temperature regime (T eff < 4800 K), and we refine the determination of the parameters of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 53 publications
(87 citation statements)
references
References 112 publications
2
83
0
1
Order By: Relevance
“…Since we see in Figure 18 that for most of the library (∼ 90%) the rms difference between the observed and interpolated spectra is < 5% we can feel confident that the stellar parameters from Prugniel et al (2011) and Sharma et al (2016) are internally self-consistent. We looked at Figure 18 separately for the MILES and IRTF spectra and found that the recovery is about the same for the majority of the stars.…”
Section: Quality Of Interpolationmentioning
confidence: 79%
See 4 more Smart Citations
“…Since we see in Figure 18 that for most of the library (∼ 90%) the rms difference between the observed and interpolated spectra is < 5% we can feel confident that the stellar parameters from Prugniel et al (2011) and Sharma et al (2016) are internally self-consistent. We looked at Figure 18 separately for the MILES and IRTF spectra and found that the recovery is about the same for the majority of the stars.…”
Section: Quality Of Interpolationmentioning
confidence: 79%
“…Throughout this work we use the stellar parameters determined by Prugniel et al (2011) and Sharma et al (2016) instead of those reported by Cenarro et al (2007). The stellar parameters determined by Cenarro et al (2007) were determined heterogeneously, depending on which additional literature data was available for a given star.…”
Section: Sample Selectionmentioning
confidence: 99%
See 3 more Smart Citations